Clinicopathological Profile of Head and Neck Cancer Patients in a University Hospital, Bangladesh - Talukdhar, Sajib Kumar; Alam, Sarwar; Bari, Md Abdul; Sharmin, Sadia; Shams, Mohammad Jahan; David, Arnob Barua (Bangladesh Medical Journal, 2021)
In Bangladesh, the head and neck cancer is one of the most prevalent cancers. The goal of this study was to assess at the clinicopathological characteristics of individuals with head and neck cancer. This descriptive, cross-sectional study was conducted from July to December 2018, 286 patients with head and neck cancer were included at Bangabandhu Sheikh Mujib Medical University (BSMMU), Department of Clinical Oncology. A pre-made questionnaire was used to collect data from patients during face-to-face interviews. The mean age of the patients was 56.27 (±12.23) years. The bulk of the cases (77.6%) were male, and the most of the patients consumed tobacco (86%). The most common histological type among the patients was squamous cell carcinoma (92%). In terms of primary tumor location, the oral cavity (36%) was the most prevalent. Patients were most often found in stages III (32.2%) and IV (34.6%). In conclusion, head and neck cancer occurs mainly in males and tobacco users. Squamous cell carcinoma is the most frequent histological form, with the oral cavity as the main location of tumors. The majority of the patients are in advanced stages. Bangladesh Med J. 2021 January; 50(1) : 23-26